Diffusion in Solids - Shewmon, Paul (The Minerals, Metals & Materials Series,, 2016)
This book offers detailed descriptions of the methods available to predict the occurrence of diffusion in alloys subjected to various processes. Major topic areas covered include diffusion equations, atomic theory of diffusion, diffusion in dilute alloys, diffusion in a concentration gradient, diffusion in non-metals, high diffusivity paths, and thermo- and electro-transport.